2020
DOI: 10.13106/jafeb.2020.vol7.no9.527
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Capabilities, Environmental Dynamism and Small and Medium Enterprises’ Internationalization Level

Abstract: Authors acknowledge the support given by Zhejiang Gongshang University and would like to thank Malaysian SME Corporation and MATRADE officials for providing assistance in data collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…An organization must be proactive not only in detecting environmental signals but also seize opportunities immediately to be successful. Ali et al (2020) argues that a company, to be successful, must continuously scan its environment to adapt to it. Environmental uncertainty has a negative impact on organizations, especially on cash flow, return on investment, and market share.…”
Section: Environmental Dynamism As Moderatormentioning
confidence: 99%
See 1 more Smart Citation
“…An organization must be proactive not only in detecting environmental signals but also seize opportunities immediately to be successful. Ali et al (2020) argues that a company, to be successful, must continuously scan its environment to adapt to it. Environmental uncertainty has a negative impact on organizations, especially on cash flow, return on investment, and market share.…”
Section: Environmental Dynamism As Moderatormentioning
confidence: 99%
“…However, environmental scanning alone will not lead to better performance without learning from the organization. Ali et al (2020) added that organizations need to adapt to changes in the environment but information and knowledge are needed. Thus the third hypothesis is proposed as follows:…”
Section: Environmental Dynamism As Moderatormentioning
confidence: 99%
“…In their research on the internationalization of Finnish companies, Cadogan et al [16] found that market dynamism has a significant positive moderating impact on the relationship between export market-oriented behavior and export performance whereas Ali et al [49] argued underlined that unfavorable environmental dynamism had a negative impact on the internationalization level of Malaysian SMEs. Managers with GM deal effectively with dynamism and complexity of multicultural business environments [50], identify and respond quickly to changes in international business environment [51].…”
Section: Moderating Role Of Export Market Dynamismmentioning
confidence: 99%
“…If it is appropriate, it is necessary to make a new plan in order to achieve the business development objectives, but if it is not appropriate, then it is necessary to find the root cause of the non-conformity and include it in the action plan for the next period of time, so that the financial management can continue to be carried out on an ongoing basis. This is explained by Ali et al (2020;Iborra et al 2020;Saunila, 2020) that financial statements play a very important role in businesses of any scale, in addition to being a reference for business owners in making decisions, also especially to obtain an overview of the company's financial performance, profit or loss. Likewise on the micro, small and medium scale, good and orderly records will help a business actor to know what transactions his business has made during a certain period.…”
Section: Figure 2 Edu Finance Model For Msmesmentioning
confidence: 99%
“…With fairly rapid economic growth, as in 2020 the economic growth will reach 7.08 percent, this condition is also accompanied by the development of business that continue to grow and develop in Sidoarjo District. The great potential of Sidoarjo District will be meaningless if it is not accompanied by its empowerment strategy, especially the MSME actors themselves in seizing and creating competitiveness for their products in the market (Ali et al 2020;Iborra et al 2020;Saunila, 2020).…”
Section: Introductionmentioning
confidence: 99%